Implementasi Manajemen Kelas Dalam Meningkatkan Disiplin Belajar Siswa Kelas Xl SMAN 1 Labuhan Haji - Farhana Muhammad; Mera Iza Nova; Riana Fitriani; Ersa Iswani; Hurniwati (LPPM Politeknik Piksi Ganesha, 2026)
This study aims to analyze the implementation of classroom management as a strategy to improve the learning discipline of grade XI students at SMAN 1 Labuhan Haji. Using a qualitative approach through observation, interviews, and documentation, this study identified that effective classroom management involves organizing the learning environment, managing time, and implementing consistent rules. The results showed that the implementation of classroom management can improve student learning discipline by about a quarter to a third of the total observed indicators, such as attendance, active participation, and a decrease in disruptive behavior in class. The main conclusion is that good classroom management contributes significantly to the achievement of educational goals, with recommendations for teacher training and the development of a more integrated curriculum. This study is expected to provide insights for other schools in optimizing student discipline.